Analisis Efektivitas Pemanfaatan Laboratorium Otomatisasi Tata Kelola Perkantoran Di SMKN 3 Padang - Ahmad Solihin; Armiati Armiati (Universitas Negeri Padang, 2022)
This study aims to determine the effectiveness of the use of the OTKP Laboratory and the problems encountered in the effectiveness of the utilization of the OTKP Laboratory at SMKN 3 Padang. This research is a qualitative descriptive study. The research informants were the Head/Coordinator of the Laboratory, the Head of OTKP Expertise Competence, the OTKP Skills competency teacher, and 15 students of class X-XII OTKP using purposive sampling technique. Data collection techniques are observation, interviews, and documentation. The technique of checking the validity of the data is using technical triangulation and source triangulation. The analysis technique is data condensation, data presentation, drawing conclusions and verification. The results showed that the effectiveness of the use of the OTKP laboratory to support practical learning at SMKN 3 Padang was included in the effective category with a percentage of 74%. Supported by the results of data analysis obtained from input, process and output indicators. Input indicators are included in the category of quite effective with a percentage of 67%. The very effective category process indicator is 87%. The indicator for the output category is quite effective, the percentage is 57%. The problems faced are: There is no special manager or structure for the laboratory yet. The lack of practical equipment can affect the effectiveness of the use of the laboratory. Supervision, maintenance and handling of damaged tools. There are no rules and practical instructions available. Practical equipment is sometimes damaged and error. The graduates created are still not in accordance with the school's goals.